2023
DOI: 10.1002/ohn.303
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Embolization Techniques in the Treatment of Juvenile Nasopharyngeal Angiofibroma: A Systematic Review

Abstract: ObjectivePreoperative embolization has proven beneficial in the surgical treatment of juvenile nasopharyngeal angiofibromas (JNA). However, the consensus for the best embolization practices remains unclear. This systematic review seeks to characterize the reporting of embolization protocols throughout the literature and to compare differences in surgical outcomes.Data SourcesPubMed, Embase, and Scopus.Review MethodsStudies investigating embolization in the treatment of JNA from 2002 to 2021 were selected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Embolisation reduces bleeding to a large extent due to the increased vascularity of the tumour. [ 3 ] However, bleeding encountered during functional endoscopic sinus surgery (FESS) is also from the richly vascularised capillary beds of the sinonasal mucosa. Larger vessels are not usually the cause of bloody fields in FESS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Embolisation reduces bleeding to a large extent due to the increased vascularity of the tumour. [ 3 ] However, bleeding encountered during functional endoscopic sinus surgery (FESS) is also from the richly vascularised capillary beds of the sinonasal mucosa. Larger vessels are not usually the cause of bloody fields in FESS.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Various techniques like a reverse Trendelenburg position, use of tranexamic acid, control of heart rate (HR) and blood pressure by α-agonists and β-blockers, propofol infusion[ 2 ] and preoperative embolisation have been described to control bleeding during endoscopic nasal surgery. [ 3 ] Few studies have described the anaesthesia management of JNA. [ 4 5 6 7 8 ] However, a bundle approach has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous factors may limit the utility of TAE, and therefore, our technique combining TAE with DAE is safe and may aid in resection. 1,2 Although several studies have demonstrated that DPE is safe and effective, the existing literature is limited, especially in regard to Onyx. Pooled data does not demonstrate a statistically significant benefit.…”
Section: Discussionmentioning
confidence: 99%
“…There is significant variation regarding embolization practices with a wide range of different techniques described and a limited basis for expert recommendations to guide decision making. 1,2 Direct puncture embolization (DPE) using an elastic polymer comprised of ethylene-vinyl alcohol copolymer or "Onyx" (Medtronic, Minneapolis, Minnesota) has been shown to be a safe and effective technique for vascular tumors. 3 As an embolic agent, Onyx offers advantages over n-Butyl-cyanoacrylate (nBCA), including more controlled delivery time, a slower rate of polymerization, and longer working time.…”
Section: Introductionmentioning
confidence: 99%
“…In cases where the tumor has an extensive supply from the internal carotid artery (ICA) branches, endovascular embolization carries a high risk of ischemic complications due to the reflux of microparticles or ethylene-vinyl alcohol copolymer (EVOH). In these situations, direct tumor puncture followed by embolization using EVOH or acrylic glue would presumably be an excellent alternative for promoting total or near-total tumor devascularization [5,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%